Diversity of life - Starr, Cecile (Brooks/Cole / Thomson, 2004)
This "Evolution and Biodiversity" section of a seven-part collection of volumes titled "Diversity of Life" addresses prokaryotes and viruses, protistans, plants, fungi, invertebrate and vertebrate animals, and biodiversity. Abundant pedagogical tools from detailed color illustrations to review questions and self- quizzes